THE INTELLECTUAL DEVELOPMENT OF THE THEORIES OF THE ORGANIZATION (World Economics and Finance Bulletin, 2022)
Many researchers and thinkers have been talking about organizations and the importance of studying them in scientific ways based on clear foundations, and the purpose of this scientific study was to enable both the organization and the individuals working in it to reach their goals. The development that the world has reached has increased the complexity between the organization and the individuals working in it, and accordingly the organization must learn about the behavior of individuals and the factors affecting this behavior, and individuals must have a comprehensive knowledge of the organization and the foundations and rules on which it is based, which contributed greatly to the diversity of theories that talk about this relationship and try to reach a general and comprehensive formula for it, and the follower of the development of organizational theories, their construction and methods of formulation knows that these theories have developed greatly, and they included traditional theories in addition to human theories, and finally modern theories. Given the complexity of these theories, I chose to talk about them in order to identify them, and to show their most important contributions in the field of interpreting work in the organization